Composite material for deck and preparation method thereof

By adding chopped glass fiber, toughener and rare earth stearate to the composite material for deck, and using composite light stabilizers to improve the weather resistance of the material, the poor toughness, insufficient impact resistance and weather resistance of the existing materials are solved. The problem of insufficient properties has achieved high weather resistance, toughness and aesthetic composite materials.

CN119490722APending Publication Date: 2025-02-21BEIJING ZHONGCHUAN ECONOMIC TECH DEV CO +1

Patent Information

Application Number
CN202411653145.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The existing composite materials for decks have poor toughness, insufficient impact resistance, easy to appear floating fibers, insufficient weather resistance, and easy to turn white and yellow.

Method used

Using composite materials including polypropylene, chopped glass fiber, toughener, rare earth stearate, compatibility agent, antioxidant and composite light stabilizer, through low molecular weight benzotriazole light stabilizer and high The mixing and compounding of the molecular weight hindered amine light stabilizer and masterbatches made of polypropylene to improve the weather resistance and toughness of the material.

Benefits of technology

It achieves high weather resistance, excellent toughness and high impact resistance of composite materials, beautiful appearance, and is suitable for a variety of climate environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005141483360000091
    Figure BDA0005141483360000091
  • Figure BDA0005141483360000092
    Figure BDA0005141483360000092
  • Figure BDA0005141483360000101
    Figure BDA0005141483360000101
Patent Text Reader

Abstract

The invention relates to a composite material for a deck and a preparation method thereof, belongs to the technical field of composite materials, and solves the problems that the composite material for the deck in the prior art is easy to break in the installation process due to poor toughness and insufficient impact resistance, and is easy to whiten and yellow due to insufficient weather resistance. The invention provides a composite material for a deck. The composite material comprises polypropylene A, chopped glass fibers, a flexibilizer, rare earth stearate, a compatilizer, an antioxidant and a composite light stabilizer, wherein the composite light stabilizer is a master batch prepared by mixing and compounding a low-molecular-weight benzotriazole light stabilizer and a high-molecular-weight hindered amine light stabilizer and then banburying with polypropylene B. The composite material is high in strength and toughness matching degree, and is not easy to break during installation; and the environment tolerance is good, the weather resistance can reach 4-5 levels, the appearance of the floating fiber reaches a superior level, and the floating fiber can be widely applied to decks of various aircrafts and other structures or appearance parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a composite material for a deck and a preparation method thereof. Background Art

[0002] As a general-purpose plastic, polypropylene is widely used in industry, agriculture, medical fields, such as industrial pipelines, automotive interior and exterior decoration, ship instruments, etc., due to its advantages of low cost, low density, high strength, good chemical resistance, good processing technology, and easy recycling. Polypropylene has become one of the fastest-growing varieties among the five general-purpose plastics.

[0003] Filling general plastics with high-strength fibers such as glass fiber and basalt fiber is one of the important means of engineering general plastics. Designers often use glass fiber reinforced polypropylene to replace some engineering plastics or metal materials. However, glass fiber reinforced polypropylene materials usually have the appearance defect of floating fibers, which makes them difficult to use in the appearance parts of products. At the same time, glass reinforced polypropylene has poor toughness and impact resistance, and is prone to breakage during the matching and installation of parts. At the same time, the addition of glass fiber will lead to poor weather resistance, and long-term exposure to the outside world will easily avoid whitening and yellowing.

[0004] In the shipbuilding industry, since ships are in contact with water for a long time, especially with seawater, metal materials are easily corroded and strict anti-corrosion measures are required, which are costly and have high metal density. Therefore, in the design of some small ships, such as fishing boats, racing boats, and sightseeing boats, engineering plastics are used to replace some metals for some structural parts and appearance parts, such as deck accessories, handrails, etc.

[0005] Glass fiber reinforced polypropylene material is one of the preferred materials in the shipbuilding industry due to its high cost performance. However, glass fiber reinforced polypropylene has poor toughness, is prone to floating fibers on the surface, and has poor long-term weather resistance. These shortcomings limit its widespread use. Summary of the invention

[0006] In view of the above analysis, an embodiment of the present invention aims to provide a composite material for a deck and a preparation method thereof, so as to solve at least one of the problems of existing composite materials for decks, such as poor toughness, insufficient impact resistance resulting in easy breakage during installation, easy appearance of floating fibers, insufficient weather resistance and easy whitening and yellowing.

[0007] The present invention provides a composite material for a deck, the composite material comprising polypropylene A, chopped glass fiber, a toughening agent, rare earth stearate, a compatibilizer, an antioxidant and a composite light stabilizer;

[0008] The composite light stabilizer is a master batch prepared by mixing and compounding a low molecular weight benzotriazole light stabilizer and a high molecular weight hindered amine light stabilizer and kneading with polypropylene B, and the effective mass content of the light stabilizer in the master batch is 40-60%.

[0009] Specifically, the components of the composite material are as follows by mass percentage: polypropylene A 60-90%, short glass fiber 5-35%, toughening agent 1-15%, rare earth stearate 0.1-2%, compatibilizer 1-5%, antioxidant 0.1-2%, and composite light stabilizer 0.1-1%.

[0010] More preferably, polypropylene A is 70-85%, short-cut glass fiber is 10-30%, toughening agent is 3-6%, rare earth stearate is 0.5-1%, compatibilizer is 2%, antioxidant is 0.5%, and composite light stabilizer is 0.6-1%.

[0011] Specifically, the molecular weight of the low molecular weight benzotriazole light stabilizer is in the range of 200 to 500, and the molecular weight of the high molecular weight hindered amine light stabilizer is in the range of 2000 to 4000.

[0012] Specifically, the mass ratio of the low molecular weight benzotriazole light stabilizer to the high molecular weight hindered amine light stabilizer is 1:0.5-2.

[0013] Specifically, the brand of the low molecular weight benzotriazole light stabilizer is UV-326 or UV-234; the brand of the high molecular weight hindered amine light stabilizer is 944.

[0014] Specifically, the particle size of the masterbatch is in the range of 3 to 5 mm; the polypropylene A and the polypropylene B are mutually soluble; or the polypropylene A and the polypropylene B are the same resin.

[0015] Specifically, the polypropylene A is a block copolymer polypropylene, and under the test conditions of 230° C. and 2.16 kg, the melt flow rate is 5 to 90 g / 10 min.

[0016] Specifically, the chopped glass fibers are alkali-free chopped glass fibers treated with a silane coupling agent, and the chopped length is 3 to 5 mm and the diameter is 8 to 15 um.

[0017] Specifically, the toughening agent is one or more of high-density polyethylene, linear low-density polyethylene, ethylene-butene copolymer, ethylene-octene copolymer and hydrogenated styrene-butadiene-styrene block copolymer.

[0018] Specifically, the compatibilizer is one or more of maleic anhydride grafted polypropylene, POE grafted maleic anhydride and styrene grafted polypropylene.

[0019] Specifically, the rare earth stearate is cerium stearate or lanthanum stearate.

[0020] Specifically, the antioxidant is a compound of a main antioxidant and an auxiliary antioxidant;

[0021] The primary antioxidant is hindered phenol and / or hindered amine;

[0022] The auxiliary antioxidant is one or more of phosphites, thiodipropionates and thiols.

[0023] The present invention also discloses a method for preparing the composite material, which specifically comprises the following steps:

[0024] S1: Weigh polypropylene, toughening agent, rare earth stearate, compatibilizer, antioxidant and composite light stabilizer according to mass ratio and put them into a high-speed mixer, stir at room temperature for 10 to 30 minutes, speed: 480 to 1200 rpm;

[0025] S2: adding the mixed materials in step S1 to the main feeding port of a twin-screw extruder, adding the glass fibers weighed according to the weight ratio to the side feeding port of the twin-screw extruder, fully plasticizing and mixing at 190-230° C., extruding, cooling and granulating, to obtain the composite material for the deck.

[0026] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:

[0027] 1. The composite material has good weather resistance, and the weather resistance level can reach level 4 to 5. It is suitable for use in various climate environments and has a wide range of application scenarios.

[0028] The present invention adds a low molecular weight benzotriazole light stabilizer and a high molecular weight hindered amine light stabilizer to the composite material, and then mixes and compounds them with polypropylene B to prepare a master batch; wherein the high molecular weight light stabilizer has anti-migration property, and can maintain the long-term weather resistance of the material, and the small molecular light stabilizer easily migrates to the surface, and can maintain the short-term weather resistance of the composite material, so this type of compounded light stabilizing additive not only ensures the short-term weather resistance of the material, but also ensures the long-term weather resistance of the material. That is to say, even if the surface of the composite material gradually wears out as the deck is used, the composite material can still maintain good weather resistance.

[0029] 2. The composite material has good toughness and high impact resistance, with a notched impact strength of ≥20kJ / m 2 The present invention adopts a resin with excellent comprehensive performance as a matrix, and adds short chopped glass fibers and a toughening agent to further improve the strength and toughness of the material, thereby obtaining a composite material with excellent toughness and high impact resistance.

[0030] 3. The composite material has good fluidity, little or no floating fibers, and beautiful appearance. The present invention adopts a matrix resin with moderate fluidity, so that the components in the composite material are evenly mixed, and the internal structural defects of the material are little or no; by adding rare earth stearate, the acidic substances generated by oxidation during the polyolefin processing can be neutralized and the processing and lubrication properties of the composite material can be improved, and the floating fiber performance of the material can also be improved, greatly improving the appearance of the composite material.

[0031] In the present invention, the above-mentioned technical solutions can also be combined with each other to achieve more preferred combination solutions. Other features and advantages of the present invention will be described in the subsequent description, and some advantages can become obvious from the description, or can be understood by practicing the present invention. The purpose and other advantages of the present invention can be achieved and obtained through the contents particularly pointed out in the description. DETAILED DESCRIPTION

[0032] The preferred embodiments of the present invention are described in detail below. The embodiments of the present invention are used to illustrate the principles of the present invention but are not used to limit the scope of the present invention.

[0033] The invention provides a composite material for a deck, comprising polypropylene A, chopped glass fibers, a toughening agent, rare earth stearate, a compatibilizer, an antioxidant and a composite light stabilizer; wherein the composite light stabilizer is a master batch prepared by mixing and compounding a low molecular weight benzotriazole light stabilizer and a high molecular weight hindered amine light stabilizer and kneading with polypropylene B, wherein the effective mass content of the light stabilizer in the master batch is 40-60%, for example, 40%, 45%, 50%, 55%, 60%.

[0034] Specifically, the components of the composite material are as follows by mass percentage: polypropylene A 60-90%, short glass fiber 5-35%, toughening agent 1-15%, rare earth stearate 0.1-2%, compatibilizer 1-5%, antioxidant 0.1-2%, and composite light stabilizer 0.1-1%.

[0035] More preferably, polypropylene A is 70-85%, short-cut glass fiber is 10-30%, toughening agent is 3-6%, rare earth stearate is 0.5-1%, compatibilizer is 2%, antioxidant is 0.5%, and composite light stabilizer is 0.6-1%.

[0036] Among them, the role and content of each component are determined as follows:

[0037] Polypropylene A and chopped glass fiber: Polypropylene A is used as the resin matrix, and chopped glass fiber has a reinforcing effect on polypropylene composite materials. If the glass fiber content is too little, the reinforcing effect is not obvious, and if the glass fiber content is too high, it will lead to serious floating fibers.

[0038] Toughening agent: Toughening agent is used to increase the notched impact strength of composite materials and improve the toughness of composite materials. If the toughening agent content is too low, it cannot form a continuous phase inside the material and has no toughening effect. If the content is too high, the material strength will decrease and the material will be too soft.

[0039] Rare earth stearate: Rare earth stearate is a multifunctional additive. First, it can neutralize the acidic substances produced by the oxidation of polyolefins during processing. Second, it can improve the processing and lubrication properties of composite materials. When added to the glass fiber system, it can improve the floating fiber performance of the material.

[0040] Compatibilizer: Glass fiber is an inorganic substance and has poor bonding ability with polymer resin. Compatibilizer can increase the bonding force between glass fiber and polypropylene resin and improve the compatibility between them.

[0041] Antioxidant: Its main function is to prevent the composite material from being oxidized and degraded during the extrusion and injection molding process.

[0042] Composite light stabilizer: High molecular weight light stabilizer is resistant to migration and can maintain the long-term weather resistance of the material. Small molecule light stabilizer easily migrates to the surface and can maintain the short-term weather resistance of the composite material. Therefore, this type of compounded light stabilizer ensures both the short-term weather resistance and the long-term weather resistance of the material.

[0043] The above-mentioned components promote each other, such as the structural reinforcement effect of polypropylene A and chopped glass fiber; the improvement of the bonding force of glass fiber by the compatibilizer; the composite light stabilizer provides excellent comprehensive weather resistance on the one hand, and polypropylene B dissolved in polypropylene A can further strengthen the resin matrix and improve the stability and uniformity of the composite material on the other hand.

[0044] Specifically, the molecular weight range of the low molecular weight benzotriazole light stabilizer is 200-500, and the molecular weight range of the high molecular weight hindered amine light stabilizer is 2000-4000; when the molecular weights of the above two light stabilizers meet the above requirements, the composite material has good comprehensive weather resistance.

[0045] Specifically, the mass ratio of the low molecular weight benzotriazole light stabilizer to the high molecular weight hindered amine light stabilizer is 1: 0.5 to 2. Too high or too low a compounding ratio may result in damage to short-term or long-term weather resistance, resulting in a decrease in comprehensive weather resistance.

[0046] Specifically, the brand of the low molecular weight benzotriazole light stabilizer is UV-326 or UV-234; the brand of the high molecular weight hindered amine light stabilizer is 944.

[0047] Specifically, the particle size range of the composite light stabilizer masterbatch is 3 to 5 mm; the polypropylene A and polypropylene B are mutually soluble; or polypropylene A and polypropylene B are the same resin. In the preparation process of the composite material, the masterbatch made of polypropylene B needs to be evenly mixed with the resin matrix formed by polypropylene A. If the particle size of the light stabilizer masterbatch is too small, it is easy to form a sand fall phenomenon, resulting in uneven dispersion of the light stabilizer in the material, thereby affecting the weather resistance of the product. The good compatibility of polypropylene A and polypropylene B is to ensure that the final composite material is evenly distributed and has balanced performance. Otherwise, defects such as uneven internal structure of the composite material may occur.

[0048] Specifically, the polypropylene A is a block copolymer polypropylene, and under the test conditions of 230°C and 2.16kg, the melt flow rate is 5-90g / 10min. The melt flow rate of the resin represents the fluidity. The better the fluidity, the better the uniformity of the mixing of the components, but it will lose certain mechanical properties. After experimental verification, when the melt flow rate is 5-90g / 10min, the comprehensive performance of the composite material is relatively balanced.

[0049] Specifically, the chopped glass fibers are alkali-free chopped glass fibers treated with a silane coupling agent, and the chopped length is 3 to 5 mm and the diameter is 8 to 15 um.

[0050] Specifically, the toughening agent is an ethylene-octene copolymer toughening agent with a density range of 0.86-0.87 g / cm 3 , the melt index is 1-2g / 10min (test conditions: 190℃, 2,16kg). This type of toughening agent has good compatibility with the resin matrix and can play a good toughening role.

[0051] Specifically, the compatibilizer is maleic anhydride grafted polypropylene with a grafting rate of 0.5-1.0%. Such a grafting rate-modified compatibilizer can significantly improve the bonding force between the chopped glass fibers and the matrix resin.

[0052] Specifically, the rare earth stearate is cerium stearate or lanthanum stearate. These two rare earth stearates have stable performance, good dispersibility and relatively low economic cost.

[0053] Specifically, the antioxidant is a compound of a main antioxidant and an auxiliary antioxidant;

[0054] The primary antioxidant is hindered phenol and / or hindered amine;

[0055] Exemplarily, the primary antioxidant is one or more of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1010), n-octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate (1076), and 2,2,6,6-tetramethyl-4-piperidinyl benzoate.

[0056] The auxiliary antioxidant is one or more of phosphites, thiodipropionates and thiols;

[0057] Exemplarily, the secondary antioxidant is one or more of tris(2,4-di-tert-butyl)phenyl phosphite (168), bis(2,4-dicumylphenyl)pentaerythritol diphosphite (S-9228), and distearyl thiodipropionate (DSTP).

[0058] Specifically, the compounding ratio of the antioxidants can be adjusted with reference to the prior art. For example, the mass ratio of the primary antioxidant to the secondary antioxidant is 1:1-5.

[0059] The present invention also discloses a method for preparing the composite material, which specifically comprises the following steps:

[0060] S1: Weigh polypropylene, toughening agent, rare earth stearate, compatibilizer, antioxidant and composite light stabilizer according to mass ratio and put them into a high-speed mixer, stir at room temperature for 10 to 30 minutes, speed: 480 to 1200 rpm;

[0061] S2: adding the mixed materials in step S1 to the main feeding port of a twin-screw extruder, adding the glass fibers weighed according to the weight ratio to the side feeding port of the twin-screw extruder, fully plasticizing and mixing at 190-230° C., extruding, cooling and granulating, to obtain the composite material for the deck.

[0062] Specifically, the composite light stabilizer can be prepared by a commonly used masterbatch mixing process. The core control parameters are the compounding ratio of the light stabilizer and the particle size of the masterbatch. Other process parameters can be selected and adjusted according to actual needs with reference to the existing technology.

[0063] Examples and Comparative Examples

[0064] In the composite material formulations of the examples and comparative examples, the copolymerized polypropylene resins were provided by Lanzhou Petrochemical and SK Chemicals, with trade names of SP179 and BX3500, respectively.

[0065] The glass fiber was provided by Taishan Glass Fiber Co., Ltd.: brand: CS249A-10C; the short cut length was 4mm and the diameter was 10um. The toughening agent was ethylene-butylene elastomer produced by LG Chemical, brand: LC168; the rare earth stearate was provided by Tongrun Nano Technology, the main component of which was cerium stearate; the compatibilizer maleic anhydride grafted polypropylene was provided by Jiayirong Company, brand name CMG9801; the antioxidant was provided by BASF and British ICE Company, brand names Irganox1010, Irganox 168 and Negonox DSTP.

[0066] Light stabilizer: The brand of low molecular weight benzotriazole light stabilizer is UV-326; the brand of high molecular weight hindered amine light stabilizer is 944;

[0067] High molecular weight hindered amine light stabilizer and low molecular weight benzotriazole light stabilizer were mixed with copolymerized polypropylene with a melt index of 30g / 10min (230℃*2.16kg) in a ratio of 1:2, 1:1 and 2:1 respectively and kneaded into masterbatch for use, with an effective mass content of 50%. The comparative light stabilizer was commercially available industrial grade UV 3808.

[0068] Table 1 Examples and Comparative Examples Formula (wt.%)

[0069]

[0070] Table 2 Composite light stabilizer (masterbatch) parameters in the embodiment

[0071]

[0072] The composite material was prepared using the following process:

[0073] S1: Weigh polypropylene, toughening agent, rare earth stearate, compatibilizer, antioxidant and composite light stabilizer according to mass ratio and put them into a high-speed mixer, stir at room temperature for 10 to 30 minutes, speed: 480 to 1200 rpm;

[0074] S2: adding the mixed materials in step S1 to the main feeding port of a twin-screw extruder, adding the glass fibers weighed according to the weight ratio to the side feeding port of the twin-screw extruder, fully plasticizing and mixing at 190-230° C., extruding, cooling and granulating, to obtain the composite material for the deck.

[0075] Performance evaluation:

[0076] The plastic granules prepared by the above method are placed in a blast drying oven at 100°C for 2 to 3 hours, and then the dried granules are injection molded on an injection molding machine to prepare samples. The test standards and methods are as follows:

[0077] Tensile strength: According to ISO 527, the sample size is 170×10×4mm dumbbell specimen, and the tensile speed is 5mm / min.

[0078] Flexural strength and flexural modulus: According to ISO 178, the specimen size is 80×10×4 mm, the bending speed is 2 mm / min, and the span is 64 mm.

[0079] Charpy notched impact strength: carried out in accordance with ISO 179, the specimen size is 80×10×4mm, and the notch depth is 1 / 3 of the specimen width.

[0080] Weather resistance: Tested in accordance with SAE J2527, the test time is 3000h, and the results are judged according to the color difference level.

[0081] Floating fiber performance: injection molded Volkswagen K31 fine leather pattern sample, visually observe the floating fiber effect.

[0082] The comprehensive performance of the material is judged by the tested material notched impact strength, tensile strength, flexural strength, flexural modulus, weather resistance and appearance performance.

[0083] Table 3 Performance test results of embodiments and comparative examples

[0084]

[0085]

[0086] From the comparison between Examples 2 and 5 and Comparative Examples 1 to 2, it can be seen that the addition of cerium stearate rare earth compound can significantly improve the surface appearance of the glass fiber system. The higher the rare earth compound content, the more obvious the improvement of the floating fiber on the surface.

[0087] It can be seen from Examples 2 and 4 and Comparative Examples 1 to 2 that the application of impact-resistant polypropylene can significantly improve the impact resistance of the material. The higher the content of the toughening agent, the higher the notched impact and toughness of the composite material.

[0088] It can be seen from Examples 1 to 6 and the comparative example that the composite light stabilizer masterbatch can obtain a good comprehensive weather resistance effect (i.e., a long-lasting weather resistance effect), and 0.3 parts of effective mass content of the composite light stabilizer can achieve the effect of 0.5 parts of the commercially available UV3808 light stabilizer. In addition, when the content of the polymer light stabilizer and the small molecule light stabilizer in the composite light stabilizer masterbatch is 1:1, the weather resistance of the composite material is the best.

[0089] The composite material provided by the present invention has the same strength and toughness as existing materials, and slightly improved impact resistance, which can meet the use requirements of various aircraft decks or external structural parts. At the same time, compared with existing materials, the weather resistance and appearance performance of the composite material provided by the present invention are significantly improved.

[0090] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by any technician familiar with the technical field within the technical scope disclosed by the present invention should be covered within the protection scope of the present invention.

Claims

1. A composite material for a deck, characterized in that: The composite material comprises polypropylene A, chopped glass fibers, a toughening agent, rare earth stearate, a compatibilizer, an antioxidant and a composite light stabilizer; The composite light stabilizer is a master batch prepared by mixing and compounding a low molecular weight benzotriazole light stabilizer and a high molecular weight hindered amine light stabilizer and kneading with polypropylene B, and the effective mass content of the light stabilizer in the master batch is 40-60%.

2. The composite material according to claim 1, characterized in that The components of the composite material are calculated by mass percentage: 60-90% polypropylene A, 5-35% chopped glass fiber, 1-15% toughening agent, 0.1-2% rare earth stearate, 1-5% compatibilizer, 0.1-2% antioxidant and 0.1-1% composite light stabilizer.

3. The composite material according to claim 1, characterized in that The molecular weight range of the low molecular weight benzotriazole light stabilizer is 200-500, and the molecular weight range of the high molecular weight hindered amine light stabilizer is 2000-4000.

4. The composite material according to claim 1, characterized in that The mass ratio of the low molecular weight benzotriazole light stabilizer to the high molecular weight hindered amine light stabilizer is 1:0.5-2.

5. The composite material according to claim 1, characterized in that The particle size of the masterbatch is in the range of 3 to 5 mm; the polypropylene A and the polypropylene B are mutually soluble; or the polypropylene A and the polypropylene B are the same resin.

6. The composite material according to claim 1, characterized in that The polypropylene A is a block copolymer polypropylene, and under the test conditions of 230° C. and 2.16 kg, the melt flow rate is 5 to 90 g / 10 min.

7. The composite material according to claim 1, characterized in that The toughening agent is one or more of high-density polyethylene, linear low-density polyethylene, ethylene-butene copolymer, ethylene-octene copolymer and hydrogenated styrene-butadiene-styrene block copolymer; The compatibilizer is one or more of maleic anhydride grafted polypropylene, POE grafted maleic anhydride and styrene grafted polypropylene.

8. The composite material according to claim 1, characterized in that The rare earth stearate is cerium stearate or lanthanum stearate.

9. The composite material according to claim 1, characterized in that The antioxidant is a compound of a main antioxidant and an auxiliary antioxidant; The primary antioxidant is hindered phenol and / or hindered amine; The auxiliary antioxidant is one or more of phosphites, thiodipropionates and thiols.

10. A method for preparing the composite material according to any one of claims 1 to 9, characterized in that: The specific steps include: S1: Weigh polypropylene, toughening agent, rare earth stearate, compatibilizer, antioxidant and composite light stabilizer according to mass ratio and put them into a high-speed mixer, stir at room temperature for 10 to 30 minutes, speed: 480 to 1200 rpm; S2: adding the mixed materials in step S1 to the main feeding port of a twin-screw extruder, adding the glass fibers weighed according to the weight ratio to the side feeding port of the twin-screw extruder, fully plasticizing and mixing at 190-230° C., extruding, cooling and granulating, to obtain the composite material for the deck.

Citation Information

Patent Citations

  • Weather resistant polypropylene composite material and its preparation method and uses

    CN103509247A

  • Low-floating fiber glass fiber reinforced polypropylene composite material and preparation method thereof

    CN103772813A

  • Good-appearance glass fiber reinforced polypropylene composite material as well as preparation method and application thereof

    CN112759836A

  • Scratch-resistant, precipitation-resistant and light-aging-resistant glass fiber reinforced polypropylene composite material for automobile stand column and preparation method thereof

    CN116063796A

  • Shock-absorbing, noise-reducing and low-emission long glass fiber reinforced polypropylene composite material with good surface appearance for automotive trim and preparation method thereof

    CN117186541A

Cited By

  • PP composite material and preparation method and application thereof

    CN120157987A